(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper presents the impact of variables on the quality of audit quality of road construction projects in Vietnam conducted by the State Audit of Vietnam. The study uses a regression model after testing the Cronbach Alpha scale and exploratory factor analysis EFA. The research data is based on the survey results of 232 subjects belonging to the Department of General, State Audit of Region I, and specialized IV and V of the State Audit of Vietnam. The result shows that six factors have a positive influence on the audit quality of road traffic construction projects, including (1) Legal environment for the audit of road construction projects in Vietnam, (2) The factor belongings to the audit unit are the investor units, (3) the auditor, (4) the working conditions of the state auditor of Vietnam, (5) the time audit, (6) Quality control of audits of road traffic construction projects by the State Audit of Vietnam